Reverse micelle extraction of erythromycin with mixed surfactant anionic and zwitterionic - Siti Norazimah, Mohamad Aziz (2019)
Most of the studies on reverse micelle extraction have been performed by using single anionic surfactant bis(2-ethylhexyl) sulfosuccinate sodium salt (AOT). However, the bio-molecules hosted in AOT reverse micelle were reported to be negatively affected by strong electrostatic interactions and high consumption of surfactant needed. Therefore, the addition of zwitterionic SB3-12 surfactant to the AOT reverse micellar was proposed for the extraction of erythromycin. This study aimed to observe the stability of mixed micelle formed based on the thermodynamic parameters which can be a potential method for antibiotic extraction. The kinetic parameter in the forward transfer was investigated, where the mass transfer kinetic, adsorptions mechanisms as well as optimum erythromycin extracted were determined. The experimental data were analyzed using Two-film theory, Langmuir, Freundlich and Sips isotherm model and the best fitted isotherm model was then determined using error analysis. For the optimization of forward extraction, a systematic experimental design including One-factor-at-time (OFAT) and full factorial design was used in the initial screening process to determine the significant variables factors. The optimized condition in forward extraction was further used in backward extraction. The factor effecting of backward extraction and kinetic mass transfer during recovery have been investigated. The CMCmix show a lower value in the range of 0.7-5.7 g/L suggests a superior surface activity compared to single surfactant. The negative value of ΔGm, ΔGads and ΔGoex indicate that the adsorption process was spontaneous and mixed reverse micelle formed was thermodynamically stable. The result proved that the addition of SB3-12 increase the stability of mixed micelle formed which provided a better microenvironment for bio-molecules. The two-film theory is appropriate for the mass transfer kinetic of erythromycin in forward extraction and the mass transfer kinetic was found to be controlled by interface solubilisation and the diffusion of the erythromycin in the aqueous phase boundary layer. The best fitting isotherm for erythromycin transfer was Langmuir isotherm, which is demonstrated by the highest values of coefficient of determination and was confirmed by three types of error analysis. The results of full factorial design (FFD) indicated that the AOT concentration, zwitterion fraction and pH of the aqueous phase, are the significant factors in forward extraction. The optimum values obtained for the forward transfers were AOT concentration, 80.7 g/L; zwitterion fraction, 0.24; and pH of aqueous, 4.7 with the optimum erythromycin transfer at 95.70 % was attained. It can be concluded that the highest erythromycin solubilisation was successfully obtained even with a low AOT surfactant which reflects the synergy between AOT and SB3-12. For the backward extraction, the extraction rates generally two orders slower than forward extraction, however, equilibrium time was found to be faster than the conventional method previously reported. The backward optimum conditions namely isopropanol v/v 3.9%; NaCl concentration, 26.5 g/L; and pH of aqueous 8.4 fulfill the conditions to successfully obtain a higher erythromycin recovery (95.01%). In backward extraction, pH was found to be significant which promotes backward extraction since erythromycin was easily to release from the mixed reverse. The anionic erythromycin predominates at higher pH, causes repulsion with the surfactant which promotes backward transfer.